Comparative Proteomic Analysis of Different Parts of Taenia Hydatigena - Cai, Mengting; Li, Yating; He, Guitian; Guo, Xiaola; Zhang, Shaohua; Yan, Lujun; Zhang, Jing; Ding, Juntao (Frontiers in Veterinary Science, 2021)
Taenia hydatigena, a globally distributed parasite, is a canine tapeworm and causes huge economic losses in the food industry. Using LC-MS/MS, the proteomes of T. hydatigena cyst scolex, designated as CS, and the cyst without the scolex, designated as CWS, were profiled and a total of 764 different proteins were identified, 664 of which were identified in CS, 412 identified in CWS and 312 in both. Comparative analysis revealed that CS had more abundant proteins associated with the growth and development, whilst CWS had more abundant proteins constituting a scaffolding and protective extracellular matrix. Consistent with the sequencing data, the abundance of the 5 selected proteins was validated to be higher in CWS than CS by Western blotting. The current data will provide a clue for further pinpointing a role of these proteins in the biology of T. hydatigena.